FROM SOUND TO MEANING: COGNITIVE INTERPRETATION OF IMITATIVE WORDS IN ENGLISH AND KARAKALPAK PROVERBS - Bayimbetova, Mekhriban Berdibaevna (ILIM hám JÁMIYET, 2026)
The article examines imitative words in English and Karakalpak from a cognitive-phonosemantic point of view. Comparative analysis reveals universal tendencies and specific phonetic adaptations of imitatives, as well as the contribution of imitatives to conceptualization in proverbs.